Utilization of Mechanization in the Process of Yield Transporting in Oil Palm Plantations - Rinanda Filsofi Siregar, Kurnia; Nurkhoiry, Ratnawati; Prima Sani Nasution, Zulfi; Akmal Agustira, Muhammad; Amalia, Rizki (Jurnal Penelitian Kelapa Sawit, 2025)
The area of oil palm plantations in Indonesia is increasing from 14.0 million ha in 2017 to 16.8 million ha in 2022, which implies an increase in the need for harvesting and maintenance labour. Currently, in Indonesia, it is increasingly difficult to find trained field labour, especially in harvesting and loading Fresh Fruit Bunches (FFB) in the palm oil industry. In the industrial era 4.0, the use of mechanisation is a potential solution to overcome labour scarcity in the agriculture and plantation sectors. Mechanisation in harvest management involves the use of tools such as: tractor scissor lift grabber, quick tractor, crawller dump, along-along, wintor and truck bin system which functions to evacuate FFB from the collection point (TPH) to delivery to the palm oil mill (PKS). This study aims to evaluate the advantages and disadvantages of the use of mechanisation in the process of transporting production and analyse its financial feasibility through the NPV, IRR, B/C and PP analysis methods. The calculation results showed that the truck bin system obtained an NPV value of Rp 424 million, IRR 21.38%, B/C 1.21, PP 5 years. tractor scissor lift grabber obtained NPV IDR 433 million, IRR 22.5%, B/C 1.28, PP 5 years, quick tractor obtained NPV IDR 39 million, IRR 23.91%, B/C 1.11, PP 3 years, wintor reached NPV IDR 45 million, IRR 26.05%, B/C 1.27, PP 3 years, and Along-along recorded NPV IDR 78 million, IRR 212.1%, B/C 1.49, PP 1 year. The results of this study show that mechanisation is technically and economically feasible in oil palm plantations.